Aflasafe product TZ01 and TZ02 for Tanzania - CGIAR Research Program on Agriculture for Nutrition and Health (2017)
Aflasafe TZ01 and Aflasafe TZ02, two biocontrol products developed for use in maize and groundnut in Tanzania, were approved by the regulatory authority of Tanzania, Plant Protection Services, Biological Control Agents Registration and Control in 2018. Both products are ready for uptake by a private sector company.